Perspektif Socio-Legal: Adaptasi Berkehidupan Warga Desa & Pengungsi Rohingya di Indonesia - Rosmalinda, Rosmalinda; Desiandri, Yati Sharfina; Khairunnissa, Siti; Syam, Farhans Mahendra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Living in a village with Refugees could develop various conflicts neither from refugees nor villagers. The research question arises on the adaptation strategies of villagers to live with the refugees in their village in regard to achieve SDGs Number 16,3,4 & 5. The approach used in this service is socio-legal. The findings show that there are challenges faced by the villagers; (a) incomprehension of villagers living near to Emergency Refugee Camp; (b) tendency of social jealousy from villagers to refugees; and (c) uncertain time for refugee leaving to third country. There were two activities to achieve the results; Conducting pre-post test and legal lecture which involved the village/sub district/district/provincial Government and villagers concerning Law and Refugees. The findings showed that the objectives were achieved due to (a) Increased knowledge of participants about refugees; (b) The presence of village / sub-district / district and provincial officials, IDCs, UNHCR and IOM as participants and resource persons; In conclusion, these two factors provide the ability of villagers to adapt and mitigate conflicts in living side by side with refugees. However, local government and IDC support is needed to UNHCR and IOM to immediately place refugees in temporary camps with access to clean water.